Developmental Changes in Endosperm of Germinating Castor Bean Independent of Embryonic Axis - Huang, Anthony H. C. (1974)
Dry castor bean (Ricinus communis) seeds were cut transversely into halves and the half without the embryonic axis was placed in moist vermiculite at 30 C for 5 days. The development of the endosperm in the half-bean was found to be qualitatively similar to that in the whole seedling in the appearance of various enzymes of gluconeogenesis, the accumulation of glucose and sucrose as the end products of fat utilization, and the development of subcellular structure. It is concluded that during germination of castor bean, the embryonic axis does not directly control the developmental changes in the endosperm.